Initial experience of a self‐expanding transcatheter aortic valve with an outer pericardial wrap: The United Kingdom and Ireland Implanters' registry. Issue 7 (11th November 2019) - Dowling, Cameron; Firoozi, Sami; Panoulas, Vasileios; Dalby, Miles; Kashyap, Mavin N.; Kabir, Tito; Kalogeras, Konstantinos; Buch, Mamta H.; Levy, Richard; Chowdhary, Saqib; Saraf, Smriti; Roberts, David; et al.
Abstract: Objectives: The United Kingdom and Ireland Implanters' registry is a multicenter registry which reports on real‐world experience with new transcatheter heart valves. Background: The Evolut PRO (Medtronic, Minneapolis, MN) transcatheter aortic valve is a self‐expanding transcatheter aortic valve with an outer pericardial wrap, designed to minimize paravalvular regurgitation. Methods: Between July 2017 and December 2018, clinical, procedural, and 30‐day outcome data were prospectively collected from all patients receiving the Evolut PRO valve across nine participating centers in the United Kingdom and Ireland. The primary efficacy outcome was the Valve Academic Research Consortium‐2 (VARC‐2)‐defined endpoint of device success. The primary safety outcome was the VARC‐2‐defined composite endpoint of early safety at 30 days. Results: A total of 317 patients underwent implantation. Mean age was 81.8 ± 6.4 years and Society of Thoracic Surgeons Predicted Risk of Mortality Score 5.5 ± 1.8%. Iliofemoral access was used in 99.1% of patients. Device success was 91.2%. Mean gradient was 7.6 ± 4.7 mmHg and effective orifice area 1.9 ± 0.7 cm 2 . The incidence of moderate paravalvular regurgitation was 1.7% and there was no severe paravalvular regurgitation. A new permanent pacemaker was implanted in 17.8% of patients without a pacemaker at baseline. Early safety was demonstrated in 92.7%. At 30 days, all‐cause mortality was 0.6%, stroke 3.8%, and major vascular complication 2.8%. Conclusions: Real‐world experience of the Evolut PRO transcatheter aortic valve demonstrated favorable procedural success, safety, valve function, and incidence of new permanent pacemaker implantation.